인문학을 활용한 대학의 인성교육과정 분석과 개선방향 - 이하준(Lee, Ha-Jun); 이찬주(Lee, SeoIn) (교양교육연구, 2015)
이 논문의 목적은 인문학을 활용한 대표적인 대학들의 인성교육과정의 운영실태와 교육과정을 분석하고 개선방향을 제시하는 데에 있다. 인문학에 기초해 인성교육과정을 운영하는 대표적인 대학은 고전교육 중심, 인간학 중심의 인성교육으로 분류할 수 있다. 고전교육의 경우는 다시 서양고전 중심과 동양고전 중심, 원전 텍스트 발췌중심과 재해석 중심으로 나눌 수 있다. 이들 대학들은 각각 인성함양이라는 교육목표를 구현하려고 하지만, 운영주체, 교육과정 편성의 목적설정과 운영 및 내용, 비교과 인성교육의 연계 등에서 차이를 보여준다. 인문학을 활용한 인성 교육과정이 더 나은 성과를 거두기 위해서는 독립된 인성교과목의 신설과 기존의 인문학을 활용한 인성교육과정과의 연계성 강화, 인성교육전문과 교육과정전문가 그리고 인문학 전문가에 의한 교육과정 설계와 운영, 인문학 활용의 인성교육을 위한 특화된 교수-학습방법론과 교육효과 측정도구의 계발, 인성교육과정의 다변화와 입체화, 인성 키워드를 활용한 교재계발, 일반 인성교육과정과 인문학을 활용한 인성교육과의 유기적 결합, 이론중심과 실천지향적 인성 교육과정과의 관계 재설계, 마지막으로 전문교수요원들의 확보가 요구된다. The purpose of this paper is to analyze the Program and Curriculum for humanistic education of most Korean universities and to suggest a direction of improvement. Korean Universities operating humanistic education curriculum generally focus on classics education or human education. In the case of classics education, It is also divided into the classification centered on Western classics, Oriental classics, model from original texts, and interpretation learning model of original texts. Each University aims to humanistic cultivation. but each shows its difference in operating body, curriculum contents and goal of education, and connection between official and unofficial curriculum, respectively. To get outcomes of humanistic education curriculum, the followings are requested: humanistic classes need to be established independently. It has to be consolidated for connectivity with an existing Curriculum of humanistic education, cooperation of a curriculum expert and humanistic education specialist, design and operation of curriculum by humanistic education expert. Then, evaluation method and special methodology for character education, diversification and dimensionality of curriculum for character education, course material according to key-words, combination of curriculum for humanistic education and another course of humanities, redesign related with theory and practice well, and finally procurement of professor resources and support plan need to be improved. KCI Citation Count: 20